Strategies of the General Election Commission in Reducing Voter Abstention and Increasing Public Participation in Regional Head Elections: A Case Study of the 2024 Local Election in Bima City - Kurniati; Rifai; Salahuddin; Nurfarhati (KOMUNITAS, 2025)
The study reveals that the Bima City General Election Commission (KPU) implemented a comprehensive set of strategies to reduce voter abstention and enhance participation in the 2024 regional election. These efforts included direct face-to-face outreach, segmented voter education, the strategic use of social and electronic media, and the installation of electoral information materials across urban and peripheral areas. Collaboration with religious leaders, community figures, and Democracy Volunteers significantly expanded the reach and credibility of political education, particularly among first-time voters, women, and marginalized groups. The findings show that although the number of registered voters increased compared to 2018, voter turnout experienced a slight decline from 84.13% to 84.04%, influenced by low political literacy, political apathy, economic constraints, and the mobility of young voters. Overall, the study concludes that KPU’s integrated outreach model effectively sustained high participation levels while highlighting persistent challenges requiring targeted policy interventions.